Hypertension in Associated with COVID-19 - Irene Louise Hutabarat; Iche Andriany Liberty (Fakultas Kedokteran Universitas Sriwijaya, 2022)
The novel coronavirus infection (COVID-19), now a worldwide public health concern is associated with varied fatality. Patients with chronic underlying conditions like hypertension have shown worst outcomes. Hypertension is a multifactorial disease and a public health burden, as it is a risk factor for diseases like stroke, coronary artery disease, and heart failure. As one of the most important public health problems in the 21st century, hypertension affects more than one billion individuals worldwide. Hypertension is a common comorbidity in COVID-19 patients. However, the association of hypertension with the severity and fatality of COVID-19 remain unclear. Hypertension is a major risk factor regarding the severity and fatality of COVID-19, and the RAAS plays an important role in COVID-19 infection since SARS-CoV-2 can lead to a dysregulation of the system by reducing the ACE2 expression. Hypertension may also affect the prognosis of COVID-19 illness. The severity rate of COVID-19 in hypertensive patients was much higher than in non-hypertensive cases. A systematic literature search was conducted using several databases on studies that assess hypertension and outcome in COVID-19. Composite of poor outcome, comprising of mortality, severe COVID-19, acute respiratory distress syndrome (ARDS), need for intensive care unit (ICU) care and disease progression were the outcomes of interest. Authors independently reviewed some titles, abstracts and read full-texts of articles to identify potentially eligible studies to decide about final inclusions. This systematic review was conducted based on the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) Statement. We used six different databases: Pubmed, Clinical Key, Science Direct, Cochrane Library, Springer Link and Oxford Academic. A total of 2731 articles from the databases were identified, we got three articles that fulfill the criteria. We excluded the other studies by reading the title, abstract, and full text assessment. Hypertension was associated with the severity and mortality of COVID-19 illness. Hypertension was also independently associated with a significantly increased risk of critical COVID-19 and inhospital mortality of COVID-19.